Effects of β(3)-Adrenergic Receptor Activation on Rat Urinary Bladder Hyperactivity Induced by Ovariectomy - Kullmann, F. Aura (American Society for Pharmacology and Experimental Therapeutics, 2009)
Voiding dysfunctions, including increased voiding frequency, urgency, or incontinence, are prevalent in the postmenopausal population. β(3)-Adrenergic receptor (β(3)AR) agonists, which relax bladder smooth muscle, are being developed to treat these conditions. We utilized the rat ovariectomy (OVX) model to investigate the effect of ovarian hormone depletion on bladder function and the potential for β(3)AR agonists to treat bladder hyperactivity in this setting. OVX increased voiding frequency and decreased bladder capacity by ∼25% in awake rats and induced irregular cystometrograms in urethane-anesthetized rats. Reverse transcription-polymerase chain reaction revealed three βARs subtypes (β(1,2,3)) in bladder tissue, and immunostaining indicated β(3)AR localization in urothelium and detrusor. Receptor expression was not different in OVX and SHAM rats. The β(3)AR agonist selectivity of BRL37344 [(±)-(R(*),R(*))-[4-[2-[[2-(3-chlorophenyl)-2-hydroxyethyl]amino]propyl]phenoxy]acetic acid sodium hydrate], TAK-677 [(3-((2R)-(((2R)-(3-chlorophenyl)-2-hydroxyethyl)amino)propyl)-1H-indol-7-yloxy)acetic acid], and FK175 [acetic acid, 2-[[(8S)-8-[[(2R)-2-(3-chlorophenyl)-2-hydroxyethyl]amino]-6,7,8,9-tetrahydro-5H-benzocyclohepten-2-yl]oxy], ethyl ester, hydrochloride] was confirmed by examining the relative potency for elevation of cAMP in CHOK1 cells overexpressing the various rat βARs. Intravenous injection of each of the β(3)AR agonists (0.1–500 μg/kg) in anesthetized rats decreased voiding frequency, bladder pressure, and amplitude of bladder contractions. In bladder strips, β(3)AR agonists (10(-12)-10(-4) M) decreased baseline tone and reduced spontaneous contractions. BRL37344 (5 mg/kg) and TAK-677 (5 mg/kg) injected intraperitoneally in awake rats decreased voiding frequency by 40 to 70%. These effects were not altered by OVX. The results indicate that OVX-induced bladder dysfunction, including decreased bladder capacity and increased voiding frequency, is not associated with changes in β(3)AR expression or the bladder inhibitory effects of β(3)AR agonists. This suggests that β(3)AR agonists should prove effective for the treatment of overactive bladder symptoms in the postmenopausal population.